Kualifikasi Penginjil yang Berintegritas: Implementasi Gaya Penginjil dalam Penginjilan Masa Kini menurut Yohanes 1:19-28 - Rudy Budiatmaja (Perkumpulan Teolog Agama Kristen Indonesia, 2025)
The current article writing aims to provide a perspective overview of the criteria of an evangelist in the Gospel of John 1:19-28 to add insight into knowledge and as a reference for evangelists when carrying out the duties and responsibilities of evangelizing in the church community so that the Great Commission is fulfilled. Writing this article is focused on qualitative methods of examining literature. The results of the study state the visionary perspective of the evangelist in preparing for the coming of Christ with the characters of humility, simplicity, honesty and firmness towards sin in serving with the concept of grace and being consistent with the orientation of heavenly calling. The end of this research concludes that the qualifications of the evangelist style in integrity evangelism must be possessed by every evangelist who wants to carry out evangelistic missions such as a spiritual and natural soul, simple and honest, humble and firm against sin, visionary in nature, service with the concept of the principle of grace and integrity when facing any problems with solutions to these problems have implications for today's evangelism for every child of God and evangelists. Contribution: This research contributes by providing a comprehensive understanding of the qualifications and leadership styles of evangelists according to John 1:19-28. It offers practical insights into how these qualities can be applied to enhance integrity in contemporary evangelism. Tulisan artikel saat ini bertujuan memberikan gambaran perspektif kriteria seorang penginjil pada Injil Yohanes 1:19-28 untuk menambah wawasan pengetahuan serta sebagai referensi bagi para penginjil saat pelaksanaan tugas dan tanggung jawab pewartaan Injil dalam komunitas gereja agar tergenapinya Amanat Agung. Penulisan artikel ini terfokuskan pada metode kualitatif menelisik kepustakaan literature. Hasil penelitian menyatakan perspektif visioner yang dimiliki penginjil dalam mempersiapkan jalannya kedatangan Kristus dengan karakter kerendahan hati, kesederhanaan, kejujuran dan tegas terhadap dosa dalam melayani dengan konsep anugerah serta konsisten kepada orientasi panggilan sorgawi. Akhir riset ini menyimpulkan kualifikasi gaya penginjil pada penginjilan integritas harus dimiliki oleh setiap penginjil yang mau melakukan misi penginjilan seperti jiwa spiritual dan natural, sederhana dan jujur, rendah hati dan tegas terhadap dosa, bersifat visioner, pelayanan berkonsepkan prinsip anugerah serta berintegritas pada saat menghadapi segala permasalahan dengan solusi-solusi pemecahan masalah tersebut sangat berimplikasi pada penginjilan masa kini bagi setiap anak Tuhan dan para pemberita Injil. Kontribusi: Penelitian ini memberikan kontribusi dengan menyediakan pemahaman yang komprehensif mengenai kualifikasi dan gaya kepemimpinan penginjil menurut Yohanes 1:19-28. Penelitian ini juga memberikan wawasan praktis tentang bagaimana kualitas-kualitas tersebut dapat diterapkan untuk meningkatkan integritas dalam penginjilan masa kini.